(untitled) (CIPEEX, 2022)
HEMOGLOBIN IS A SPHEROID AND GLOBULAR PROTEIN PRESENT IN RED BLOOD CELLS WITH A FUNCTION OF GAS EXCHANGE FROM 02 OF THE LUNGS TO THE TISSUES AND CO2 FROM THE TISSUES TO THE LUNGS. ANEMIA IS A CONDITION CHARACTERIZED BY A DECREASE IN HEMOGLOBIN (HB) IN ERYTHROCYTES, WITH VALUES €‹€‹BELOW 12.0 G / DL FOR WOMEN AND 13.0 G / DL FOR MEN. THE MAIN CAUSES ARE FOR DEFICIENCY OF VITAMIN B12, FOLIC ACID AND IRON DEFICIENCY. THE OBJECTIVE WAS TO PERFORM THE CLASSIFICATION OF ANEMIA SEVERITY ACCORDING TO THE HEMOGLOBIN DOSAGES OBTAINED THROUGH THE COMPLETE BLOOD COUNT REPORTS FROM THE LABORATORY OF CLINICAL ANALYSIS OF CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA IN THE YEAR 2017. THIS STUDY IS A RETROSPECTIVE STUDY OF LONGITUDINAL CHARACTER, IN WHICH THE REPORTS OF COMPLETE BLOOD COUNT OF 2023 PATIENTS ATTENDED BY SUS WERE ANALYZED IN THE CITY OF ANÁPOLIS - GOIS, BRAZIL, PERFORMED AT THE LABORATORY OF CLINICAL ANALYZES OF UNIEVANGLICA, IN THE YEAR 2017. DATA WERE COLLECTED FROM THE DATA SHEET REGISTRY OF THE LABORATORY AND THE FILE OF REPORTS BY THE INTERNAL SYSTEM (SISLAC), THEN THE TRANSCRIPTION OF THE RESULTS WAS DONE TO A TABLE IN EXCEL FORMAT. THE WORK WAS APPROVED BY THE RESEARCH ETHICS COMMITTEE OF UNIEVANGLICA UNDER PROTOCOL NUMBER: 2,675,303 / 2018. AN ANALYSIS OF THE SEVERITY OF ANEMIA WAS MADE USING THE WORLD HEALTH ORGANIZATION CRITERIA IN 2017. IN THE DEVELOPMENT OF THIS STUDY, THE PATIENTS WERE SEPARATED INTO SIX GROUPS: CHILDREN AGED 6 MONTHS TO 4 YEARS; CHILDREN FROM 5 TO 11 YEARS OLD; CHILDREN FROM 12 TO 14 YEARS OF AGE; WOMEN OVER 15 YEARS OF AGE, MEN OVER THE AGE OF 15 YEARS. FROM THESE, A COMPARISON WAS MADE BETWEEN THE HEMOGLOBIN CONCENTRATIONS AND THE DEGREE OF ANEMIA SEVERITY, BEING ABLE TO BE CLASSIFIED AS MILD, MODERATE AND SEVERE. IN THE FIRST SAMPLE COMPOSED OF 80 CHILDREN AGED SIX MONTHS TO FOUR YEARS, THERE WAS NO SEVERE ANEMIA; AMONG THESE FINDINGS, TWO CHILDREN (2.5%) HAD MILD ANEMIA, EIGHT HAD MILD ANEMIA (10%) AND 70 HAD NO ANEMIA ANEMIA. IN ANOTHER ANALYSIS PERFORMED WITH 154 CHILDREN AGED 5 TO 11 YEARS, 153 (99.4%) OF THESE CHILDREN DID NOT PRESENT SEVERE OR MODERATE ANEMIA, ONE (0.6%) OF PATIENTS WITH MILD ANEMIA. THE NEXT GROUP CONSISTED OF 80 PEOPLE AGED 12 TO 14, OF WHOM 75 HAD NO ANEMIA AND FIVE HAD MILD ANEMIA (6.3%). THE FOLLOWING ANALYZED SAMPLE CORRESPONDS TO A TOTAL OF 1053 WOMEN OVER 15 YEARS OF AGE, OF THESE 126 SHOWED A HIGHER PREVALENCE IN MILD (11.9%), MODERATE (5.3%) AND FOUR SEVERE ANEMIAS (0.4%). IN A TOTAL OF 470 MEN OVER 15 YEARS OF AGE, 429 HAD NO ANEMIA, 35 HAD MILD ANEMIA (7.4%) AND SIX MODERATE (1.3%). PATIENTS WHO DEVELOP SEVERE ANEMIA MAY EXHIBIT SIGNS AND SYMPTOMS WHEN THE FACILITY IS GRADUAL. CONSIDERING THE ABOVE, IN THE STUDIED POPULATION IT CAN BE VERIFIED THE OCCURRENCE OF MILD AND MODERATE AND SEVERE ANEMIA.